Leveraging Synergy Between Professionalism and Development to Succeed in Teaching: A Theoretical-Empirical Review - Yu Yangyang Hailey (Ilmu Inovasi Nusantara, 2024)
The teaching profession faces increasingly complex challenges as educational demands evolve in the 21st century. One of the primary issues teachers encounter is the need to continuously enhance professionalism while engaging in ongoing professional development. This study aims to analyze the synergy between professionalism and professional development within the context of teaching as a profession, as well as how this synergy can be optimized to improve teacher performance and success. The research employs a theoretical and empirical review that combines literature analysis with case studies. This study identifies key concepts in professionalism and professional development and explores the relationship between them through empirical data gathered from surveys and interviews with teachers across various educational levels. The findings reveal a significant correlation between the level of professionalism and engagement in professional development programs with the quality of teaching. Teachers who are actively involved in professional development tend to perform better, are more adaptable to curriculum changes, and are more capable of addressing challenges in teaching. Additionally, the study finds that the synergy between professionalism and professional development enhances teacher motivation, strengthens their commitment to the profession, and ultimately has a positive impact on student learning outcomes